Africa why economists get it wrong - Jerven, Morten (London Zed Books, 2015)
For the first time in generations, Africa is spoken of these days with enthusiastic hope: no longer seen as a hopeless morass of poverty, the continent instead is described as ?Africa Rising,? a land of enormous economic potential that is just beginning to be tapped.
Includes index
Keywords: Africa